Fetotoxic risk of AT1 blockers exceeds that of angiotensin-converting enzyme inhibitors: an observational study. Issue 1 (January 2020) - Weber-Schoendorfer, Corinna; Kayser, Angela; Tissen-Diabaté, Tatjana; Winterfeld, Ursula; Eleftheriou, Georgios; Te Winkel, Bernke; Diav-Citrin, Orna; Greenall, Amanda; Hoeltzenbein, Maria; Schaefer, Christof
Abstract : Objective: The fetotoxic potential of prenatal exposure to angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin II receptor blockers (ARBs) has been known for many years. Symptoms range from transient oligohydramnios to neonatal anuria and permanent renal damage, joint contractures, hypocalvaria, lung hypoplasia and intrauterine or neonatal death. This study aims to investigate the critical gestational time for renin–angiotensin system inhibitor (RAS-I)-induced fetopathy, to quantify the fetopathy risk and to evaluate factors associated with the occurrence and severity of fetopathy. Methods: Prospectively and retrospectively ascertained RAS-I exposed pregnancies from the databases of six teratology information services were analyzed. Results: Eighty-nine pregnancies with ACE-I and 101 with ARB exposure beyond the first trimester were identified. Fifty-nine of these 190 pregnancies were classified as having evidence of RAS-I fetopathy. All pregnancies affected with fetopathy were exposed after 20 0/7 gestational weeks. Limited to prospectively enrolled cases with exposure at least 20 0/7 gestational weeks, the rate of fetopathy was 3.2% for ACE-I and 29.2% for ARB. The chance of recovery of amniotic fluid volume was higher with RAS-I discontinuation before 30 gestational weeks and with a longer exposure-free interval before delivery. Conclusion: Exposure to ARBs is associated with a higher fetopathy risk than exposure to ACE-Is. RAS-I should ideally be discontinued prior to pregnancy or immediately after recognition of pregnancy. Because symptoms may improve in cases of RAS-I-induced oligohydramnios, pregnancy should be maintained as long as there is fetal well being. Physicians and patients need to be alerted to the fetotoxic risks of RAS-I. Abstract : Supplemental Digital Content is available in the text